A new cubichnium ichnogenus and ichnospecies, Pygocephalichnium reidi, from the Pennsylvanian UNESCO World Heritage Site at Joggins Fossil Cliffs, Canada, and associated ichnotaxa - Malay, Bailey C.; Stimson, Matthew R.; King, Olivia A.; Faulkner, Sal; Hebert, Brian L.; Calder, John H.; MacRae, R. Andrew; Lucas, Spencer G. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2024)
The Carboniferous Joggins Fossil Cliffs UNESCO World Heritage Site in Nova Scotia, Canada, has long been known for its extensive paleobiodiversity. The ichnofossil record at Joggins is less known than the body fossil record. Amongst the extensive ichnological collections of the late citizen-scientist Donald Reid is a morphologically unique shrimp-shaped cubichnium (resting trace). The trace fossil is associated with a faint invertebrate trackway that leads up to the resting trace and establishes its identification as an invertebrate resting trace. The trace fossil was recovered from the upper Joggins Formation (876 m above the base), and was found in finegrained, rippled sandstones interpreted to be from an open-water to poorly drained lithofacies assemblage transition. The trace fossil slab studied here also has examples of the invertebrate resting traces Selenichnites and Rusophycus preserved in convex hyporelief; these traces are commonly attributed to horseshoe crabs and crustaceans, respectively. They co-occur in the same stratigraphic horizon with Kouphichnium trackways, interpreted to be produced by xiphosurans. The upper Joggins Formation has previously yielded body fossils of Pygocephalus shrimp preserved in organic-rich limestones and sideritic-ironstone nodules. Pygocephalus body fossils are common at Joggins, but no trace fossils have been assigned to this invertebrate, perhaps having gone unrecognized until now. The trace fossil newly described here as Pygocephalichnium reidi is interpreted to have been produced by a Pygocephalus shrimp based on its morphological similarities to known body fossils from the Joggins Formation, and we propose that this new trace fossil morphology warrants a new ichnotaxon, Pygocephalichnium reidi.